2006
DOI: 10.1590/s1807-59322006000100003
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Sensitivity of Dermatophytes to Urea

Abstract: Martins JEC, Corim SM, Arriagada GLH, Melo NT de, Heins EM. In vitro sensitivity of dermatophytes to urea. Clinics. 2006;61(1):9-14.OBJECTIVE: Urea is commonly used as a keratolytic substance in the treatment of onychomycoses to improve the penetration of antifungal drugs in the lesion sites. The aim of the present study was to investigate the inhibitory action of urea on samples of dermatophytes in vitro. METHOD: Minimum inhibitory concentration of urea was determined for 31 samples of dermatophytes cultured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Santos et al (2017) mentioned that miconazole nitrate combined with a natural product (polygodial) recorded an MIC value of 0.65 mg/L, which was higher than that reported in the presence of urea in our study. Martins et al (2006) studied the inhibitory effect of 7.5 to 40% urea on dermatophytes in vitro . It was found that 87% of the dermatophytes were susceptible to urea at 12.5%, and that only two isolates of Trichophyton spp.…”
Section: Discussionmentioning
confidence: 99%
“…Santos et al (2017) mentioned that miconazole nitrate combined with a natural product (polygodial) recorded an MIC value of 0.65 mg/L, which was higher than that reported in the presence of urea in our study. Martins et al (2006) studied the inhibitory effect of 7.5 to 40% urea on dermatophytes in vitro . It was found that 87% of the dermatophytes were susceptible to urea at 12.5%, and that only two isolates of Trichophyton spp.…”
Section: Discussionmentioning
confidence: 99%